Serum Electrolyte Changes in Chronic Renal Failure Pre and Post Dialysis - Najat Alaswad,; Manal Khalifa, (AlQalam Journal of Medical and Applied Sciences, 2025)
Chronic renal failure is a progressive decline of the kidney function leading to accumulation of toxins and fluid. Hemodialysis is a method of renal replacement therapy that is used to achieve the removal of that waste product such as creatinine and urea from blood by an artificial kidney machine. The aim of the study was to compare serum urea, creatinine, sodium, and potassium and chloride levels in chronic renal failure patients before and after dialysis. This study was conducted on 35 patients. All patients had renal failure and enter the dialysis department in Gharyan teaching hospital. It was found that the mean level of serum urea, creatinine and potassium were significant difference between pre and post dialysis. The pre-hemodialysis urea was 142.2 ± 34.1 mmol/L and post-hemodialysis urea was 45.7 ± 15.8 mmol/L. The pre-hemodialysis creatinine was 11.9 ± 3.2 mmol/L and post-hemodialysis creatinine was 4.3 ± 1.5 mmol/L. The pre-hemodialysis potassium was 5.1 ± 0.8 mmol/L and post- hemodialysis potassium was 3.6 ± 0.4 mmol/L. There is decrease in serum urea, creatinine as well the level of potassium before and after hemodialysis. While the level of serum sodium and chloride not significantly changed after hemodialysis. الفشل الكلوي المزمن هو تدهور تدريجي في وظائف الكلى مما يؤدي إلى تراكم السموم والسوائل، وبعض المخلفات الايضية، وغسيل الكلى هو طريقة من طرق العلاج التعويضي الذي يستخدم لإزالة تلك السموم والمخلفات مثل الكرياتينين، واليوريا من الدم بواسطة جهاز الغسيل الكلوي الاصطناعي. كان الهدف من الدراسة هو مقارنة مستويات اليوريا والكرياتينين والصوديوم والبوتاسيوم والكلوريد في مصل مرضى الفشل الكلوي المزمن قبل وبعد غسيل الكلى. أجريت هذه الدراسة على 35 مريضًا يعانون من القصور الكلوي في مستشفى غريان المركزي التعليمي. وجدت الدراسة أنه كان له فرق كبير في متوسط ​​مستوى اليوريا والكرياتينين والبوتاسيوم في المصل بين ما قبل وما بعد غسيل الكلوي. فكان مستوي متوسط اليوريا قبل غسيل الكلى 142.2 ± 34.1 مليمول / لتر، اما بعد الغسيل فكان متوسط اليوريا 45.7 ± 15.8 مليمول / لتر. وكان مستوي متوسط الكرياتينين قبل غسيل الكلى 11.9 ± 3.2 مليمول/لتر وبعد غسيل الكلى كان المتوسط 4.3 ± 1.5 مليمول/لتر. اما البوتاسيوم، فكان مستوي متوسطه قبل الغسيل 5.1 ± 0.8 مليمول/لتر، وبعد الغسيل الكلوي كان مستوي المتوسط 3.6 ± 0.4 مليمول/لتر. وبذلك كان هناك انخفاض ملحوظ في مستوي متوسط كلا من اليوريا والكرياتينين في المصل وكذلك مستوى البوتاسيوم قبل وبعد غسيل الكلوي، في حين لم يتغير مستوى الصوديوم والكلوريد في المصل بشكل ملحوظ بعد غسيل الكلى